2021
DOI: 10.3390/app11114873
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and Volumetric Measurements of Orbital Structures in CT Scans in Thyroid Eye Disease Classification

Abstract: This study examines the usefulness of both geometric and volumetric measurements of orbital soft tissues on CT scans to provide quantitative diagnostic guidance in image reading of thyroid eye disease (TED). Computed tomography (CT) images were obtained from 92 orbits and were classified as impaired motility (TED-IM) and normal motility (TED-NM). The TED-IM group was further divided into dysthyroid optic neuropathy (DON) and non-DON groups. There were 5 volumetric, 2 angular, and 3 ratio parameter measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The measurement method is consistent with the published literature 10 . We focused on comparing orbital parameters found in previous studies that re ect compression of the orbital apex.…”
Section: Volume Measurements Of Orbital Tissuesupporting
confidence: 83%
See 3 more Smart Citations
“…The measurement method is consistent with the published literature 10 . We focused on comparing orbital parameters found in previous studies that re ect compression of the orbital apex.…”
Section: Volume Measurements Of Orbital Tissuesupporting
confidence: 83%
“…At the base of our preliminary study 20 , we noticed that the differences between the DON patients and non-DON patients were mainly concentrated in the orbital apex, which indicated that orbital apex congestion, especially the pressure from the medial wall was the primary cause of DON. In this study, we propose and emphasize the importance of deep orbital decompression (up to the orbital apex and the orbital part of the optic canal) in patients with DON.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Volumetric measurements of extraocular muscle tissues can demonstrate the condition of apical crowding in a quantitative way and have been used as an indicator of DON. [ 25 ] Our case 1 right eye had grade 3 and left eye grade 2 apical crowding [ Figure 3a ]. In case 2, both eyes had grade 2 apical crowding [ Figure 6a ].…”
Section: Discussionmentioning
confidence: 99%